ANALISIS PERSEPSI MAHASISWA TERHADAP PEMANFAATAN CHATGPT DALAM PEMBELAJARAN DI PROGRAM STUDI BAHASA DAN SASTRA ARAB SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) MANDAILING NATAL - Hakim, Rani Ismail; Darman, Isra Hayati; Astina, Chairani (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study aims to analyze students' perceptions of the use of artificial intelligence (AI) technology, specifically ChatGPT, in Arabic language learning at the Arabic Language and Literature Study Program, STAIN Mandailing Natal. Using a mixed methods approach and an explanatory sequential design, this study collected quantitative data through a questionnaire followed by qualitative interviews to explore students' experiences. The results indicate that the majority of students experienced a significant improvement in their understanding of Arabic language material, particularly in translation and writing, thanks to ChatGPT's assistance. This technology also enhances students' motivation and learning autonomy. However, several challenges were identified, such as inaccuracies in ChatGPT's responses, limitations in understanding cultural context, and the potential for excessive reliance on technology. This study concludes that while ChatGPT offers significant benefits in the Arabic language learning process, its use must be balanced with faculty guidance and digital literacy training to ensure appropriate and responsible use. Therefore, this study recommends the development of more adaptive AI-based learning strategies and the integration of ethical guidelines in the use of technology in higher education.